A Pilot Test to Analyse the Differences of Pedestrian Thermal Comfort Between Locals and Internationals in Malacca Heritage Site. (September 2020) - Manteghi, Golnoosh; Mostofa, Tasneem; Lamit, Hasanuddin Bin
The present study aims to establish a correlation between the physiological equivalent temperature (PET) and subjective thermal sensation in the Tropics, assessing their impact on local as well as international pedestrians. The pilot test was conducted in six scenarios in the Malacca region of Malaysia. The RayMan model calculated the PET, which is further used to synthetically evaluate the thermal environment for six scenarios, each with a different river width and pavement material. The independent t-test and regression analysis determined the correlation between human thermal comfort acceptability and the thermal environment indices of outdoor spaces. Most of the outdoor thermal comfort assessments have been carried out focusing on local urban residents, while the same assessments on tourists are limited. This research provides necessary insight into the perception of outdoor microclimatic conditions in the Malacca heritage area and also identifies the perception on a few important psychological factors of these two demographic groups. An awareness of such issues would be fruitful for architects, planners and urban designers engaged in the process of designing and planning tourist destinations.